2013
DOI: 10.12691/ajphr-1-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light’s Colour Temperatures on Visual Comfort Level, Task Performances, and Alertness among Students

Abstract: Introduction: Correlated colour temperatures (CCT) of the light source in indoor environment plays an imperative role in addressing both psychological and physiological functions of the occupant. As one of the determinants of lighting quality, CCT are off particular importance which affects quality of work and in classroom learning. Objective: The aim of this study is to determine the effects of warm white light (WWL) (CCT = 3,000K), cool white light (CWL) (CCT = 4,000K) and artificial daylight (DL) (CCT=6,500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 14 publications
12
49
0
1
Order By: Relevance
“…Experimental studies have shown that exposure to higher levels of light at night leads to suppression of melatonin secretion, increase of physiological arousal, higher levels of mental consciousness and improvement of alertness and cognitive performance (Hawes et al, 2012[ 13 ]; Min et al, 2013[ 26 ]). Research findings have further demonstrated that increasing the color temperature of the light sources improves cognitive performance of night shift workers, visual performance and visual comfort of the students and sleep quality, performance and behavior of industrial staff (Viola et al, 2008[ 39 ]; Chellappa et al, 2011[ 7 ]; Shamsul et al, 2013[ 36 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that exposure to higher levels of light at night leads to suppression of melatonin secretion, increase of physiological arousal, higher levels of mental consciousness and improvement of alertness and cognitive performance (Hawes et al, 2012[ 13 ]; Min et al, 2013[ 26 ]). Research findings have further demonstrated that increasing the color temperature of the light sources improves cognitive performance of night shift workers, visual performance and visual comfort of the students and sleep quality, performance and behavior of industrial staff (Viola et al, 2008[ 39 ]; Chellappa et al, 2011[ 7 ]; Shamsul et al, 2013[ 36 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the illuminance levels on the desks are approximately 700 to 800 lx. When lights for windows zone are switched off, the results revealed that the illuminance levels on the working desks in the windows zone are in the range of 450 to 650 lx, which is more than the minimum lighting requirement in the office (Shamsul et al, 2013). In addition, the power usage of electric lights is 720 W, and the energy consumption is 5.76 kWh.…”
Section: Daylight Availability Assessmentmentioning
confidence: 99%
“…Designers must ensure that the visual comfort parameters comply with the standard of lighting design. Regarding human visual perception, the most important variables are CCT and illuminance level (Shamsul et al, 2013). Visual perception is defined as an interpretation capability of visual sensation when people visually perceive their surrounding environment.…”
Section: Lighting Design Metrics In the Game Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was also demonstrated how lighting and students' learning performance are connected, better lighting leads to an increase in students' learning motivation [41]. Because of these reasons, a hotel room that allows being customized by the guests according to their needs or desires could play an important role in promoting the hotel's revenue.…”
Section: Luminous Comfort: Meeting the Needs Of Business Travellersmentioning
confidence: 99%